Risk and Protective Trajectories, Community Context, and Juvenile Recidivism, Florida, 2015-2018 - Wolff, Kevin T. ([Verlag nicht ermittelbar], 2023)
The study examines trajectories of risk and protective factors throughout probation supervision, whether such trajectories affect the likelihood of recidivism, and how community context influences those relationships. A state-wide sample of Florida juveniles who completed probation supervision between 2015 and 2018 were included in the analysis. Probationers completed multiple risk/need assessments during their supervision, which were leveraged by the researchers, in combination with census tract information in which the youth resided, and multiple official measures of recidivism. Major categories of variables include criminal background, school records, family history, drug and alcohol use, mental health, social skills, and social disorganization and immigration levels for youth's neighborhoods. Probationer's age, sex, and race were collected as well.